BPP UTILIZATION BY FARMERS TO SUPPORT INDONESIA AS BARNS THE WORLD - Iranita Haryono; Astrini Padapi; Ayu Wulandary (Socio-Economics/Agribusiness Department, 2021)
One of the efforts to achieve national food security is by strengthening assistance and counseling to farmers as the main actors. One of the extension links closest to the community and located at the sub-district level is the Peratanian Extension Center (BPP). The function and role of BPP is developed to achieve the desired expectations, namely food self-sufficiency and improvement of farmer welfare. Therefore, there is a need for a special study to be able to determine the level of responsiveness, responsibility and quality of agricultural extension services carried out by the BPP in Sidenreng Rappang Regency. This reserch aims to determine the performance of agricultural extension agents in Sidenreng Rappang Regency in terms of the level of accountability of agricultural extension activities based on indicators of responsiveness, responsibility and quality of extension services. The research was conducted from July to October in Sidenreng Rappang Regency. This research used a survey method. Determination of the sample of this study was carried out purposively on extension workers at the local BPP. Data collected descriptively by cross tabulation. Data analysis used scoring parameters, proportion, maximum, minimum and average values. The results show that the agricultural instructor's Performance Score is 294 which is interpreted into a moderate category score, which means that the ability of the BPP is sufficient to be able to recognize the needs of the assisted farmers, is sufficient to develop extension programs / activities that are in accordance with the wishes / aspirations of local farmers, and sufficient in providing service to farmers.